Social Skill Development through Kampus Mengajar Program by English Education Study Program Students of PGRI Silampari University - Dwi Lestari; Dewi Syafitri; Yulfi Yulfi (Journal of English Education, Literature and Linguistics, 2025)
This research aimed to explore the enhancement of students’ social skills through their participation in the Kampus Mengajar program. The research focused on four core skill areas: Communication Skills, Emotion Regulation Skills, Cognitive Skills, and Social Problem Solving Skills using Douglas, Smith, and Johnson’s (2020) theory. A descriptive qualitative method was employed with 30 students from PGRI Silampari University selected purposively as the subjects of this research. Questionnaires, interviews, and document analysis were used as instruments in collecting data. The data were analyzed thematically across 16 indicators. The findings revealed that the Kampus Mengajar program significantly contributed to the development of participants' social competencies. Notably, students demonstrated strong abilities in the four key areas of social skills Communication Skills (88,8%), Emotion Regulation Skills and Cognitive Skills (83,3%), and Social Problem Solving Skills (82,5) which were evident in their classroom interactions. The study concluded that real-world teaching experience provided a valuable context for enhancing students’ social skills.